GRAFIK PENGENDALI NON PARAMETRIK EMPIRIK - Santoso, Rukun (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2008)
Shewhart control chart is constructed base on the normality assumption of process.Â If the normality is fail then the empirical control chart can be an alternative solution. This means that the control chart is constructed base on empirical density estimator. In this paper the density function is estimated by kernel method.Â The optimal bandwidth is selected by leave one out Cross Validation method. The result of empirical control chart will be compared to ordinary Shewhart chart. Â Key words : Control chart, Kernel, Cross Validation